2017
DOI: 10.1002/slct.201702281
|View full text |Cite
|
Sign up to set email alerts
|

H‐Bonding in Water of Hydration: NIR Spectral Studies of Hydration Behavior of 1‐n‐Alkyl‐3‐metylimidazolium‐Based Bromide and Amino Acid Ionic Liquids at 298.15 K

Abstract: H‐bonding in ionic hydration is crucial for understanding various phenomena such as osmolyte effects, ion transport, electrochemical processes, etc. Ionic liquids (ILs) from the biomaterials have great affinity for protein solubility and stabilization due to hydrophobicity and hydrogen bonding ability. To explore potential use of ionic liquids, it is essential to understand hydration of ionic liquids with detailed information on H‐bonding within the water of hydration. In this context, near‐infrared spectral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…19 Near-infrared (NIR) investigations for aqueous solutions of amino acid ionic liquids (AAILs) showed that water in the hydration shell of amino acid anions makes a major contribution to the icelike structure, i.e., the hydration shell of amino acid anions is highly structured. 59 Seen in this light, the observed large hydration numbers for studied PILs are due to the cooperative H-bonding of the carboxylate functional group of anions with the surrounding water. The hydration numbers of PILs at infinite dilution (Table 9) reveal that the hydration numbers increase with an increase in the hydrophobicity of the anions of PILs, and this trend exists even at the finite concentrations studied, indicating that the hydrophobic hydration existing at infinite dilution persists even at a higher concentration although ion association occurs at the highest concentration studied (Figure 11).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…19 Near-infrared (NIR) investigations for aqueous solutions of amino acid ionic liquids (AAILs) showed that water in the hydration shell of amino acid anions makes a major contribution to the icelike structure, i.e., the hydration shell of amino acid anions is highly structured. 59 Seen in this light, the observed large hydration numbers for studied PILs are due to the cooperative H-bonding of the carboxylate functional group of anions with the surrounding water. The hydration numbers of PILs at infinite dilution (Table 9) reveal that the hydration numbers increase with an increase in the hydrophobicity of the anions of PILs, and this trend exists even at the finite concentrations studied, indicating that the hydrophobic hydration existing at infinite dilution persists even at a higher concentration although ion association occurs at the highest concentration studied (Figure 11).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, we observed large hydration numbers for amino acid ionic liquids and further showed that the observed hydration numbers are solely due to the amino acid anions, as the associated cations are only slightly hydrated. 19,59 The analysis of partial molar entropy data and enthalpy−entropy compensation effects revealed that the observed large hydration numbers for amino acid ionic liquids are due to cooperative H-bonding with and around the carboxylate functionality of amino acid anions. 19 Near-infrared (NIR) investigations for aqueous solutions of amino acid ionic liquids (AAILs) showed that water in the hydration shell of amino acid anions makes a major contribution to the icelike structure, i.e., the hydration shell of amino acid anions is highly structured.…”
Section: Discussionmentioning
confidence: 99%
“…5a1 and b1, respectively, corresponding to the absorption of 2 v 3 and v 2 + v 3 of CH groups. 58,59 For a clear comparison, the transformed spectra of homopolymer PDAAM (yellow curve) and PDAAM powder (purple curve) were also plotted in the two figures, respectively. PC1 is compared with the transformed spectra of homopolymer PDAAM, and similarities were found between them.…”
Section: Resultsmentioning
confidence: 99%
“…5a1 and b1, respectively, corresponding to the absorption of 2v 3 and v 2 + v 3 of CH groups. 58,59 For a clear Fig. 5 The first two PCs (a and b) in the region from 6200 to 5600 cm À1 , and the third (c) and sixth (d) PCs in the region from 7200 to 6400 cm À1 obtained by NPCA from the spectra: the loading (a1-d1), time scores (a2-d2), temperature scores (a3-d3) and concentration scores (a4-d4); the lines in (b3-d3) were obtained by linear fitting in two or three stages.…”
Section: Npca On Nir Spectramentioning
confidence: 99%
“…Microscopic scenarios in terms of interactions proposed from these techniques highlights ion–solvent interaction, but complete and coherent understanding in terms of weakening or strengthening of interactions between ions and water is not clear. In our laboratory the ion–ion, ion–solvent, and ion–pair interactions and hydrophobic effects have been studied using near-infrared (NIR) spectroscopy and with the help of thermodynamic properties obtained using vapor pressure, density, and speed of sound measurements. The obtained thermodynamic parameters such as osmotic coefficient, partial molar volumes, and isentropic and isothermal compressibilities infer a combination of numerous interactions, so it is complex to validate the strengthening and weakening of specific interactions responsible for their kosmotropic or chaotropic behavior of ionic liquids in aqueous medium. The observed interactions of ILs with water studied using different techniques discussed above are strongly related to H-bonding and non-H-bonding nature of ILs.…”
Section: Introductionmentioning
confidence: 99%